2005
DOI: 10.1074/jbc.m506000200
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate Inhibits Insulin Gene Expression by Altering PDX-1 Nuclear Localization and Reducing MafA Expression in Isolated Rat Islets of Langerhans

Abstract: Abnormalities in lipid metabolism have been proposed as contributing factors to both defective insulin secretion from the pancreatic beta cell and peripheral insulin resistance in type 2 diabetes. Previously, we have shown that prolonged exposure of isolated rat islets of Langerhans to excessive fatty acid levels impairs insulin gene transcription. This study was designed to assess whether palmitate alters the expression and binding activity of the key regulatory factors pancreas-duodenum homeobox-1 (PDX-1), M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(190 citation statements)
references
References 48 publications
13
176
1
Order By: Relevance
“…A lowered proinsulin mRNA level is a common feature observed in beta cell studies with combination of high glucose and excess NEFA [16]; here, in fact, proinsulin mRNA levels were 50% reduced in the ZF-Px islets. However, this is often assumed to imply a reduced rate of proinsulin production.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A lowered proinsulin mRNA level is a common feature observed in beta cell studies with combination of high glucose and excess NEFA [16]; here, in fact, proinsulin mRNA levels were 50% reduced in the ZF-Px islets. However, this is often assumed to imply a reduced rate of proinsulin production.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, in vitro and whole-animal studies have reported a direct inhibitory effect of excess NEFA, such as occurs with insulin resistance, on glucose-mediated insulin secretion [15], proinsulin biosynthesis [15,16] and beta cell survival [17,18]. Also in vitro studies have shown a synergistic toxic effect of high glucose and saturated NEFA, a process termed glucolipotoxicity, leading to beta cell dysfunction and death [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In mice lacking MafA, reduced insulin 1 and 2 gene transcription, glucose intolerance and development of diabetes mellitus was observed [12]. At least at the beta cell level the transcriptional activity of MafA seems to be regulated by either changes in MafA synthesis or by an enhanced degradation of this protein [11,16,26,48,49]. However, in the present study overproduction of MEKK1 did not decrease the amount of MafA produced in JEG cells (data not shown), arguing against a MEKK1-induced degradation of MafA.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon these studies, several mechanisms have been postulated: (a) increased β cell apoptosis via and Bcl-2), with resulting loss of downregulation of anti-apoptotic genes (Bcl XL functional cell mass [56,67], (b) loss of activity of key Pdx1 target genes whose products are involved in glucose-stimulated insulin transcription and secretion (including Glut2, glucokinase, MafA, Nkx6.1, insulin) [57,63,[68][69][70][71][72][73][74][75][76], and (d) loss of new β cell formation/regeneration [64,77]; in this regard, studies suggest that the action of glucagon-like peptide 1 (GLP1) in enhancing β cell growth and formation in the adult may rely upon activation of Pdx1 in β cells and potential precursor cell types, such as those residing within ducts [74,[78][79][80][81][82].…”
Section: Role Of Pdx1 In the Adult Pancreasmentioning
confidence: 99%
“…Although some reports in the literature have described physiologic circumstances where the distribution of Pdx1 might be cytoplasmic, it is believed that cytoplasmic sequestration may represent more a mechanism to attenuate the nuclear action of Pdx1 under physiologic or pathologic conditions, rather than to promote a specific cytoplasmic function. For example, the negative effect of fatty acids on β cell function may be related to their eventual sequestration of Pdx1 in the cytoplasm [76], whereas the positive effect of glucose on insulin transcription may be a result of its enhancement of Pdx1nuclear translocation [108]. A basic amino acid sequence with the homeodomain of Pdx1, RRMKWKK, is believed to function as the nuclear targeting sequence [109].…”
Section: Mechanism Of Pdx1 Action Posttranslational Modifications Of mentioning
confidence: 99%